MANAJEMEN DISTRIBUSI KAPSUL MINYAK BERYODIUM DI TUJUH KABUPATEN DI JAWA BARAT DAN SUMATERA SELATAN PERIODE 1997-2001 - Syarifudin Latinulu; Vita Kartika; Basuki Budiman; Sri Prihatini (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2002)
MANAGEMENT OF IODIZED OIL ADMINISTRATION IN SEVEN DISTRICTS IN WEST JAVAAND SOUTH SUMATERA DURING 1997-2002.Background: The intensification of administration of Iodized oil as a short term intervention program to combat the 100 problem have been launch more than 5 years. Since January 2001, the iodized oil program is under responsibility of the district government. Some problems araised.Objectives: To get an efficiency model of iodized oil distribution. Specific objective, to study the maximum coverage and the accuracy of distribution population target, inhibition and promoting factors of distribution.Methods: The study was crossectional and explorative. The study was done in six districts of West Java and one district in South Sumatera. Respondent were the 100 program officer. Primary data collected with interview method and secondary data collected with copying the annual data reported of primary health care, and/or notation of vilages midwive. Descriptive analysis on organisation and management flow of capsules was implemented.Results: It was found out that there were deviated target of iodized oil distribution area as well as population target which is happen in OKI, Sukabumi, and Karawang. In OKI, Iodized oil was distributed in precisely light and moderate prevalence kecamatan; and also elementary school. Planning of Iodized oil distribution not yet property running well due to some reasons. The coverage of Iodized oil distribution variated in between kecamatan (from 45,8% to 93,5 %).Conclusions: The distribution model is fairly good. The quality of data for planning still low. There are some inhibiting factors drawn synergistic effect for delying the success of iodized oil administration. The coverage of distribution is low, fund for sweeping and up-dating population target data are too restrict.Recommendations: The iodized oil distribution guide book need to be updated. Administration of iodized oil in the light prevalence kecamatan should be sloped.Keywords: iodized oil management, distribution model, decentralization planning and population target